Q‐collect: results of a European Union project to improve the status of reference collections important for plant health. (19th July 2016) - Bonants, P.; Streito, J.‐C.; Elphinstone, J.; Pottier, P.; Robert, V.; Bluemel, S.; van der Blom, M.; Gentit, P.; de Vos, P.; Petter, F.
Abstract : The ability of National Plant Protection Organizations (NPPOs) and their affiliated laboratories to quickly and reliably detect and identify organisms is critical for the effective performance of phytosanitary measures. Plant pest diagnostics is also essential to support the phytosanitary certification of consignments of plants and plant products exported from the EU. Access to reference material has been identified as a limitation on the ability of laboratories to develop and validate diagnostic tests and ensure the reliability of diagnostics. The EU FP7 Q‐collect project worked to establish the state of the art of current phytosanitary collections, to identify gaps and propose minimum quality standards, to facilitate access to specimens and to design and build networks of reference collections. The main results of the project are presented in this paper.